Students’ Intuitive and Analytical Thinking in the Mathematics Study through the Integration of STAD and Environmental Islamic Jurisprudence (Fiqh) - Abdillah, Abdillah; Mastuti, Ajeng Gelora; Rijal, Muhammad; Rahman, Muhajir Abd. (Al-Jabar: Jurnal Pendidikan Matematika, 2020)
The success of a learning process depends on the teacher’s mastery of materials, strategies, and media. Teachers need to possess high creativity to maintain their students’ interest and motivation in learning. The integration of effective learning models and appropriate media, such as using plastic waste as realia, can be one of the alternatives to improve the quality of learning. This study also aimed to examine students' awareness of environmental issues. The quantitative and qualitative data of the study were collected simultaneously to answer the research problems. Interviews were conducted during the implementation of the learning process and quizzes. A pre-experimental one-shot case study design was employed to gather the quantitative data which were then analyzed descriptively. The results of the current study showed that the students' intuitive thinking started to develop in phase 3, where they were asked to identify the type of plastic glass they were holding. Phase 4 that allowed the students to separate parts constructing the glass, determine the name of each part, and set a point of view or the purpose underlying the material presented was the phase where the students performed an analytical thinking process. In phase 5, the students were allowed to solve a mathematical problem using analytical thinking. The interaction between students' intuitive and analytical thinking shown in the identification and labeling of each type of three-dimensional form will be discussed in this article